'Closed world, wounds open. Open world, wounds closed': metacultural commentaries on digital media and youth suicide in Jan Komasa's Suicide Room. (2nd October 2021) - Alvarez, M. F.
ABSTRACT: Despite the attention funnelled towards cinematic representations of suicide, there is a dearth of writings on filmic depictions of cybersuicide, especially those relating to adolescents and young adults. Using cultural discourse theory's five radiants of meaning, this article examines metacultural commentaries surrounding digital media and youth suicide that are embedded in Jan Komasa's fiction film, Suicide Room . The film suggests that while digital communication can facilitate more authentic expressions of self, the internet's technical affordances can also undermine the gravity of self-destruction by rendering private pain trivial or spectacular. Suicide Room taps into concerns about within-group purification by showing members of the virtual community engage in ritualistic behaviours that glorify collective fascination with and desire for death – behaviours that are typically found in what scholars have called 'online negative enabling support groups'. The film has a strong anti-suicide message, showing death by suicide to be excruciatingly painful. Though it reiterates popular tropes about youth, media, and mental health, it avoids the deterministic view so common in entertainment media that locates blame in technology, instead highlighting digital media's inextricable connections to place-based systems and relational networks.